Ralstonia eutropha, containing high poly-β-hydroxybutyrate levels, regulates the immune response in mussel larvae challenged with Vibrio coralliilyticus. Issue 84 (January 2019) - Van Hung, Nguyen; De Schryver, Peter; Dung, Nguyen Viet; Nevejan, Nancy; Bossier, Peter
Abstract: Marine invertebrates rely mainly on innate immune mechanisms that include both humoral and cellular responses. Antimicrobial peptides (AMPs), lysozyme and phenoloxidase activity, are important components of the innate immune defense system in marine invertebrates. They provide an immediate and rapid response to invading microorganisms. The impact of amorphous poly-β-hydroxybutyrate (PHB-A) (1 mg PHB-A L −1 ) on gene expression of the AMPs mytimycin, mytilinB, defensin and the hydrolytic enzyme lysozyme in infected blue mussel larvae was investigated during " in vivo " challenge tests with Vibrio coralliilyticus (10 5 CFU mL −1 ). RNAs were isolated from mussel larvae tissue, and AMPs were quantified by q-PCR using the 18srRNA gene as a housekeeping gene. Our data demonstrated that AMPs genes had a tendency to be upregulated in challenged mussel larvae, and the strongest expression was observed from 24 h post-exposure onwards. The presence of both PHB-A and the pathogen stimulated the APMs gene expression, however no significant differences were noticed between treatments or between exposure time to the pathogen V. coralliilyticus . Looking at the phenoloxidase activity in the infected mussels, it was observed that the addition of PHB-A significantly increased the activity. Highlights: Our study is innovative because for the first time. Specific primers are developed for 4 antimicrobial peptides in Mytilus edulis larvae. The effect of PHB in blue mussel larvae has been related to gene expression. The antimicrobial peptide defensin was identified in Mytilus edulis larvae